Analysis of the main socioeconomic indicators of the Ecuadorian Agricultural Sector (2000-2022) - Pino Peralta, Sergio (2024)
The agricultural sector in Ecuador, a key player in the country’s economic system, is currently facing important challenges that threaten the sustainability of production. Consequently, the objective of this research was to analyze the main socioeconomic indicators of the Equatorian agricultural sector during the 2000-2022 period. Using a descriptive methodology with quantitative and analytical-synthetic methods, information was sourced from BCE and INEC. Results show that agricultural activities contribute 7.92% to Ecuador’s GDP, generate 35% of foreign exchange earnings, and yield 94.84% of the food consumed by the population. However, agricultural production is concentrated on a few primary goods. In addition, the agricultural frontier has been reduced in recent years, there is evidence of a process of disinvestment by the State in the agricultural sector, and the agricultural GDP growth rate shows a downward trend. Therefore, current administrations in Ecuador have not attempted to change to a model that would honor the efforts of the rural population.